Current Understanding of the Role of PPAR<svg style="vertical-align:-4.698pt;width:11.35px;" id="M1" height="16.012501" version="1.1" viewBox="0 0 11.35 16.012501" width="11.35" xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg"> <g transform="matrix(.022,-0,0,-.022,.062,10.1)"><path id="x1D6FE" d="M478 372q0 -39 -31 -97t-61 -98t-78 -98q-45 -55 -73 -102q-13 -79 -13 -197q-11 -11 -43.5 -25.5t-53.5 -15.5l-15 17q5 35 26 101.5t47 123.5q8 72 -1.5 174.5t-37.5 178.5q-14 37 -29 37q-20 0 -67 -65l-25 21q37 60 73 90.5t63 30.5q47 0 72 -112q13 -56 17.5 -141.5 t0.5 -143.5h2q155 193 155 297q0 26 -12 47q-5 8 -5 15q0 16 12.5 27t29.5 11q21 0 34 -21t13 -55z" /></g> in Gastrointestinal Cancers - Zou, Bing; Qiao, Liang; Wong, Benjamin C. Y. (PPAR Research, 2009)
Numerous studies have indicated that PPARγ plays multiple roles such as in inflammation, cell cycle control, cell proliferation, apoptosis, and carcinogenesis, thus PPARγ contributes to the homeostasis. Many in vitro studies have showed that ligand-induced activation of PPARγ possess antitumor effect in many cancers including CRC. However, the role of PPARγ in gastrointestinal cancers, especially in colorectal cancer, is rather controversial. Nevertheless, some recent studies with the positive results on the possible application of PPARγ ligands, such as Bezafibrate or Rosiglitazone in gastrointestinal cancers, have suggested a potential usefulness of PPARγ agonists in cancer prevention and therapy. In this review, the authors discuss the recent developments in the role of PPARγ in gastrointestinal cancers.